Aromatic nitration using aqueous nitric acid - D.J. Belson (1989)
The rates of nitration of benzene, toluene, anisole, p-xylene and mesitylene in aqueous nitric acid have been determined for concentratians in the range 24-41 mol % HNO3 and at temperatures between 293 and 333K. Correlation of rate constants with values of acidity function confirms that the mechanism of nitration in aqueous nitric acid is similar to that in aqueous Sulphuric acid....